Berlin prehospital or usual delivery of acute stroke care – Study protocol. Issue 6 (August 2017) - Ebinger, Martin; Harmel, Peter; Nolte, Christian H; Grittner, Ulrike; Siegerink, Bob; Audebert, Heinrich J
Rationale: Prehospital stroke care in specialized ambulances increases thrombolysis rates, reduces alarm-to-treatment times, and improves the prehospital triage. Preliminary analyses suggest cost-effectiveness. However, scientific proof of better functional outcome compared to usual care is still lacking. Aim: To prove better functional outcomes after deployment of the Stroke Emergency Mobile compared to regular ambulances. Sample size estimates: A sample size of 686 patients will be required in each arm (Stroke Emergency Mobile group vs. regular care) to detect a difference regarding the primary outcome with 80% power at a two-sided significance level of 0.05. Methods and design: This is a pragmatic, prospective study with blinded outcome assessment. Primary outcome will be functional status as defined by modified Rankin Scale score three months after the incident event. We will include cerebral ischemia patients within a predefined catchment area in Berlin, Germany. The study population consists of patients who might be candidates for acute recanalizing treatments, with onset-to-alarm time ≤4 h, symptoms not resolved at time of ambulance arrival, and able to walk without assistance prior to the qualifying incident. About 45% of Stroke Emergency Mobile dispatches are expected to be handled by regular ambulances, since Stroke Emergency Mobile will be already in operation creating the control group. Primary outcome: Functional outcome after three months measured by the modified Rankin Scale over the entire range. Discussion: The results will inform decision makers on the effectiveness of Stroke Emergency Mobile.